Performance of high-strength and heat-resistant cast aluminum alloy and its complex shell castings for aircraft engines - QIE Juhong; XIE Feng; FENG Chao; WANG Pinghai; YU Tengfei; YANG Chaoyang; XI Honglei; XIAO Wenlong; MA Chaoli (Cailiao gongcheng)
To meet the application requirement of advanced aviation engines for complex shell castings of high-strength and heat-resistant aluminum alloys， the process and mechanical properties of a new type of the Al-Si-Cu-Mg-Sc high-strength and heat-resistant aluminum alloy are analysed in comparison with ZL101A and ZL205A cast aluminum alloys. Design and experimental verification of the metal casting process for the complex casing of the oil pump are carried out by using the high-strength and heat-resistant aluminum alloy， and the quality of the casting products is evaluated. The results indicate that the new high-strength and heat-resistant Al-Si-Cu-Mg-Sc alloy shows better casting fluidity and hot cracking resistance than the ZL205A high-strength cast Al alloy. The qualification rate of the complex shell of its metal casting oil pump is comparable to that of the same type of shell ZL101A. The average tensile strengths at room temperature of the separated test bar of casting and test specimen from casting itself of the new alloy are higher than 420 MPa， which are significantly higher than that of ZL101A alloy， while the tensile strengths at 250 ℃ are superior to ZL205A alloy. The surface quality， internal quality， airtightness， and pressure resistant performance of the casting case all meet the design requirement of the product.